The emerging role of Financial Counsellors in supporting Older Persons in financial hardship and with management of Consumer‐directed Care packages within Australia. Issue 1 (22nd November 2018) - West, Raelene; Ramcharan, Paul
Abstract: The role of financial counsellors as providers of information, support and advocacy for those in financial difficulty is a well established mechanism in the mainstream welfare landscape in Australia. In general, the role of financial counsellors is in helping people alleviate or resolve their financial difficulties through improvement of their financial literacy. It is recognised as an important component of policy responses to assist low‐income households and individuals in financial stress. The use of financial counsellors for older persons (i.e., those aged 65+ years) however appears to be underutilised. Financial hardship and abuse of older persons within our community are becoming key issues as the population of Australia "ages". Existing evidence also suggests that service providers alone do not have adequate skills to address these issues. This paper firstly examines the development of financial counselling in Australia. It then examines the newly emerging role of financial counselling in supporting older persons in addressing barriers to financial literacy and then in navigating the complex landscape of aged care service provision. The current finacialisation, marketisation and complexities of consumer‐directed care are identified as key contextual factors. The paper will then discuss an evaluation study of the provision of financial counselling to the older person population designed to support financial hardship and navigation of the complex aged care services system. The findings of the paper are based on an evaluation of the Financial Consumer Rights Council (FCRC), Victoria: Dignity and Debt Financial Difficulty and Getting Older initiative. This pilot initiative included older persons from both community‐based and aged care residential facilities in one regional area of Victoria. The initiative, conducted over 2016, was designed to assess the effectiveness of one‐on‐one financial counselling sessions with older persons that provided consumer advocacy and information about support services and entitlements (including hardship protections) associated with ageing. The evaluation found that the provision of financial counselling to the older person population could be a key mechanism in improving overall financial literacy, avoiding periods of financial hardship and in maintaining financial well‐being, quality of life and positive ageing. Findings also demonstrated a need for an expanded model of outreach financial counselling model to better service older persons in more isolated living environments and/or with mobility impairments living in the community, and the potential to situate offices of financial counsellors within medical centres (a space often visited by the ageing population), to co‐situate financial health check‐ups as an overall element of health and well‐being. As such, financial counselling was viewed as well‐placed to support older persons in improvement of financial literacy and in supporting navigation of the increasingly complex marketised and consumer‐directed care (CDC) landscape of aged care service provision in Australia.